Effect of annealing temperatures on TiO2 thin films prepared by spray pyrolysis deposition method - F.I.M. Fazli; N. Nayan; M.K. Ahmad; M.L. Mohd Napi; N.K.A. Hamed; N.S. Khalid (Penerbit Universiti Kebangsaan Malaysia, 2016)
Titanium dioxide (TiO2) nanoparticles thin film has been successfully synthesized by a spray pyrolysis deposition method by using an air compressor on a fluorine-doped tin oxide (FTO) substrate and was annealed at different temperature. TiO2 is the most common oxide as an electrode in dye sensitized solar cell (DSSC) which still has chances of improvements to increase its efficiency as an electrode. The efficiency of a DSSC was relatively low but modifications on every part of a DSSC were currently in research progress and an increase in adsorbed dye molecules was considered a potential. Thus, the influences of annealing temperature on structural and morphological properties of TiO2 have been studied using X-ray diffraction (XRD) and field emission scanning electron microscopy (FESEM), respectively, while the efficiency of the films in a solar cell was studied by a solar simulator. The FESEM result showed several degrees of porosity obtained by varying the annealing temperature. The crystallinity of TiO2 investigated by XRD showed that the crystallinity of the TiO2 thin films was generally unaffected by the annealing temperature. The relationship between the properties and the efficiency of the films as an electrode was also studied.